ANALISIS MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Septiani, Rida; Salsabila Rahmadina; Tri Setya Ningrum; Nur Indah Sari (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to analyze the relationship between learning motivation and students' mathematics learning outcomes. The method used is a Systematic Literature Review (SLR) of eight scientific articles from 2009 to 2025. The findings indicate that learning motivation plays a vital role in encouraging student engagement, enthusiasm, and confidence, which positively impact academic achievement. While most studies show a significant relationship between motivation and learning outcomes, some findings reveal that other factors also influence students' academic performance.